Comparative Analysis in Bonus of Floor-Area Ratio by The General Comprehensive Design System and The Urban Housing Comprehensive Design System in Tokyo - Takamizawa, Minoru; Kobayashi, Shigenori; Nam, Jin (Urban housing sciences, 1999)
The purpose of this study is to analyze the realities in the bonus of floor-area ratio by The Urban Housing Comprehensive Design System (HCDS) and The General Comprehensive Design System (GCDS), and to clarify by what factor the bonus of floorarea ratio is influenced. As resultants of the analysis, cases by HCDS have received the bonus of floor-area ratio about twice higher than cases by GCDS. From such a fact, it has been understood that the acquisition of a house floor by the bonus of floor-area ratio is a main purpose in HCDS, and a main purpose in GCDS is to make the form in the office building reasonable by easing conditions of regulation. And from analysis of variance, analysis of quantified scaling, it was found that the rate of effective open space and the zoning influenced the bonus of floor-area ratio most in HCDS, and that the easing conditions of regulation and the rate of effective open space influenced most in GCDS.